Plasma Folate, Vitamin B6 and B12 in Their Relationship to the Presence of Probiotic Strain Bifidobacterium animalis subsp. Lactis HNO19 (DR10TM) Among Indonesian Pregnant Women in Their Third Semester - Saptawati Bardosono; Noroyono Wibowo; Luciana Budiati Sutanto; Rima Irwinda; Rebecca Cannan; Angela Rowan; James Dekker (World Nutrition Journal, 2019)
Introduction Vitamin B12 plays a role during pregnancy in maintaining folate metabolism. Together with folate and vitamin B6, B12 is involved as a coenzyme in DNA synthesis and various methylation reactions in developing embryos. This study aims to compare plasma folate, vitamin B6 and B12 blood levels with respect to the presence of probiotic strain Bifidobacterium animalis subsp. lactis HNO19 (DR10TM) among pregnant women in Indonesia. Methods: This study is part of a larger study entitled “Effects of Bifidobacterium animalis subsp. lactis HNO19 (DR10TM), inulin, and micronutrient fortified milk on fecal DR10TM, immune markers, and maternal micronutrients among Indonesian pregnant women.” Further analyses were performed using independent-t test or Mann Whitney test, GLM-repeated measures and chi-square test, to compare folate, vitamin B6 and B12 intake and blood concentration during pregnancy with presence (n=22) and absence (n=55) subjects of fecal DR10TM at third trimester. Results: At the first trimesters there was no difference in plasma vitamin B6 and vitamin B12 levels between the two groups, based on the presence or absence of fecal DR10TM. However, at the second and third trimester, vitamin B6 blood concentration (p=0.034 and p=0.001) and vitamin B12 blood concentrations at the third trimester (p=0.035) were significantly higher in the fecal DR10TM positive group, while having a similar vitamin B6 and B12 intake. Conclusion: Consumption of pre- and probiotics during the periconceptional period may be a useful strategy for improving maternal vitamin B’s vitamins, especially vitamin B6 and B12 status and therefore provide benefits for the offspring’s quality of life.